Minat Mahasiswa Berinvestasi di Pasar Modal Melalui Pengetahuan Investasi, Fasilitas Online Trading, dan Religiusitas - Saputra, Anggi; Widiastuty, Erna; Febrianto, Rahmat (Akuntansi & Ekonomika, 2023)
This study aims to identify factors that influence individual or group interest in investing in the capital market, especially among Economics and Business students from universities in West Sumatra. Some of the factors that become the focus of research include the level of knowledge about investment, the availability of online trading facilities, and the level of religiosity. The population of this study were Economics and Business faculty students with active status at universities in West Sumatra using certain criteria obtained 73 respondents. The data source in this study is primary data through questionnaires. Hypothesis testing using SPSS. The results of hypothesis testing provide evidence that: (1) investment knowledge is not proven to have a significant influence on investment interest. (2) online trading facilities and religiosity have a positive and significant effect on investment interest.